Tinjauan Yuridis terhadap Pelanggaran Prinsip Keterbukaan pada PraktekWindows Dressing dalam Pasar Modal Indonesia - Hutabarat, Ribka Delila; Hasanah, Ulfia; ', Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Information disclosure is an important element for the corporate worldbecause information on the substance presents the description, notes ordescription of good for the State of the past and the latest of an enterprise andthe market effect. But in reality, not all issuers disclose information that isactually about the fact material in the prospectus.If there is a breach of the principle of disclosure by issuers then issuers willbe subject to administrative sanctions in accordance with Article 102 of TheCapital Market Laws, namely in the form of a written warning, fines, namely theobligation to pay a certain sum of money, restrictions on business activities,freezing of business activities, business license revocation, cancellation ofagreement and cancellation of registration. is an action that beautify the financialstatements of a company. This is referred to as windows dressing.Windows dressings aims to enhance your company's image so as toattract investors to make investments. The practice of dressing the windows inthe capital markets can still be said to be a reasonable course of actionthroughout the activities aimed to improve the company and not to the detrimentof others. However, the practice of dressing the windows can be categorized as acriminal offence the capital markets if such activity creates information or issuesmisleading so as to affect the market mechanism. In the event of the occurrence ofthe windows dressing, the practice of legal protection afforded to investors couldbe done in a preventive and repressive.Preventative legal protection carried out by PT. Stock Exchange by doing atemporary suspension against securities trading. While the repressive legalprotection carried out by OJK with conducting surveillance, investigation and theimposition of sanctions to any party proven to engage in the practice of cheatingor fraud in the capital market. In addition, investors who feel aggrieved may do alawsuit to the Court against the issuers that have been doing practice windowsdressing.Keywords:Investors Protection - Windows Dressing – Issuer